Comparative Prevalence of Immune Evasion Complex Genes Associated with β-Hemolysin Converting Bacteriophages in MRSA ST5 Isolates from Swine, Swine Facilities, Humans with Swine Contact, and Humans with No Swine Contact. - Samantha J Hau; Jisun Sun; Peter R Davies; Timothy S Frana; Tracy L Nicholson (PLoS ONE)
Livestock associated methicillin-resistant Staphylococcus aureus (LA-MRSA) draws concern from the public health community because in some countries these organisms may represent the largest reservoir of MRSA outside hospital settings. Recent studies indicate LA-MRSA strains from swine are more genetically diverse than the first reported sequence type ST398. In the US, a diverse population of LA-MRSA is found including organisms of the ST398, ST9, and ST5 lineages. Occurrence of ST5 MRSA in swine is of particular concern since ST5 is among the most prevalent lineages causing clinical infections in humans. The prominence of ST5 in clinical disease is believed to result from acquisition of bacteriophages containing virulence or host-adapted genes including the immune-evasion cluster (IEC) genes carried by β-hemolysin converting bacteriophages, whose absence in LA-MRSA ST398 is thought to contribute to reduced rates of human infection and transmission associated with this lineage. The goal of this study was to investigate the prevalence of IEC genes associated with β-hemolysin converting bacteriophages in MRSA ST5 isolates obtained from agricultural sources, including swine, swine facilities, and humans with short- or long-term swine exposure. To gain a broader perspective, the prevalence of these genes in LA-MRSA ST5 strains was compared to the prevalence in clinical MRSA ST5 strains from humans with no known exposure to swine. IEC genes were not present in any of the tested MRSA ST5 strains from agricultural sources and the β-hemolysin gene was intact in these strains, indicating the bacteriophage's absence. In contrast, the prevalence of the β-hemolysin converting bacteriophage in MRSA ST5 strains from humans with no exposure to swine was 90.4%. The absence of β-hemolysin converting bacteriophage in LA-MRSA ST5 isolates is consistent with previous reports evaluating ST398 strains and provides genetic evidence indicating LA-MRSA ST5 isolates may harbor a reduced capacity to cause severe disease in immunocompetent humans.